PENDIDIKAN KESEHATAN TENTANG KESIAPSIAGAAN MENGHADAPI KORBAN BENCANA TERHADAP PENGETAHUAN SISWA - Moudy Lombogia; Jon W. Tangka; Maria Terok; Femmy Lumi (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
The knowledge of students about disaster prevention emergency patients in vocational Yadika Langowan is still lacking where 80% do not know about Preparedness in facing flood victims. The lack of students' knowledge about preparedness in facing flood victims is due to the lack of exposure of students to health care about preparedness in facing flood victims. The purpose of this study was to determine the effect of health education on preparedness in the face of flood victims on student knowledge.The research design in this study was a one-group pre-experimental pre-post test design to compare knowledge before and after being given health education about preparedness to face flood victims to students' knowledge. The population in this study were all students of the Manado Cokroaminoto Vocational School and the sample was students of class X and XI 68 people who were determined by purposive sampling. Analysis with the Wilcoxon signed rank testThe results of the test have a significant effect on health education about preparedness to face flood victims to increase knowledge (p-value = 0,000; α = 0.05). The conclusion is that health education about preparedness to face flood victims increases student knowledge